Fashion Ekologis di Yogyakarta: Membangun Brand Awareness melalui Keterkaitan Diri dan Produk - Rachmahwati, Ayu (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2024)
This study delves into the brand communication strategy and the implementation of sustainability values in the small and medium-sized fashion enterprise (SME), Lori Lurik, highlighting its success in amalgamating brand identity, sustainability, and communication strategies to foster personal and emotional connections with its consumers. Grounded in the Self-congruity Theory and the Message Planning Model, Lori Lurik consistently opts for handwoven lurik fabric as its primary material, reflecting local and cultural values. Following the principles of self-congruity, Lori Lurik successfully builds brand awareness through compelling narratives on Instagram and engaging consumers in interactive quizzes. Design innovations, such as the distinctive asymmetrical features, provide differentiation in the competitive fashion industry. The utilization of leftover production materials and a zero-waste packaging strategy underscores the commitment to sustainability, while challenges in leveraging influencers serve as crucial considerations for enhancing brand awareness. This research contributes practical insights for similar SMEs, emphasizing the importance of integrating sustainability values and communication strategies to strengthen brand images in dynamic markets.